2008
DOI: 10.1016/j.jvs.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates ischemic brain damage in the delayed phase after stroke and induces messenger RNA and protein express for angiogenic factors

Abstract: Resveratrol administration by gavage provided an important neuroprotective effect on focal cerebral ischemic injury in the delayed phase. The elevated MMP-2 and VEGF levels might be important in the neuroprotective effect of resveratrol administration by inducing angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 23 publications
4
71
1
Order By: Relevance
“…Findings from several studies have demonstrated that performance of dogs in cognitive tests (including those that examine spatial memory) can be improved by various substances (including antioxidants, mitochondrial cofactors and a pharmaceutical with alpha-1 adrenergic agonist action) and by behavioural enrichment [21][22][23][24][25]. Oral administration of resveratrol has been used with success in previous studies of cognitive function in animals [3,5,9,10]. There are very few studies on the bioavailability of resveratrol in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from several studies have demonstrated that performance of dogs in cognitive tests (including those that examine spatial memory) can be improved by various substances (including antioxidants, mitochondrial cofactors and a pharmaceutical with alpha-1 adrenergic agonist action) and by behavioural enrichment [21][22][23][24][25]. Oral administration of resveratrol has been used with success in previous studies of cognitive function in animals [3,5,9,10]. There are very few studies on the bioavailability of resveratrol in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, a plant-derived phytoestrogen, may minimise the deterioration in cognitive function associated with physical and chemical damage to the brain [1][2][3][4][5][6][7]. In rats and mice, resveratrol has been found to minimise the adverse brain and cognitive changes induced by neurologically damaging events such as streptozotocin-induced diabetes [1]; percussive cerebral trauma [2]; focal cerebral ischemia (stroke) [3]; oxidative stress caused by intracerebroventricular injection of streptozotocin [4] or cochinine [5]; and neurotoxic substances used to mimic Huntington's disease [6] and Parkinson's disease [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart, resveratrol increased levels of vascular endothelial growth factor (VEGF) and its receptor FLK-1, leading to enhanced angiogenesis and reduced myocardial infarction (Fukuda et al, 2006). This protection has also been shown in the brain where administration of resveratrol elevated proangiogenic factors such as matrix metalloproteinase-2 and VEGF levels providing neuroprotection after focal ischemia in the delayed injury phase (Dong et al, 2008).…”
Section: Resveratrol-activated Pathways Protect Against Ischemic Injurymentioning
confidence: 93%
“…Resveratrol attenuates ischemic brain damage by increasing the expression of matrix metalloproteinase-2 and vascular endothelial growth factor 6) and exerting anti-oxidative, anti-inflammatory and anti-apoptotic effects 7,8) .…”
Section: Introductionmentioning
confidence: 99%